The management of anticoagulants in patients with atrial fibrillation and history of falls or risk of falls: The Liverpool AF-Falls Project. A systematic review and meta-analysis. (19th May 2022) - Galvain, T; Hill, R; Donegan, S; Lisboa, P; Lip, GYH; Czanner, G
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Johnson and Johnson Medical Background: Atrial fibrillation affects an estimated 33 million individuals worldwide and a major cause of stroke, heart failure, and death. Treatment with anticoagulants substantially reduces risk of stroke but is also associated with an increased risk of bleeding and especially intracranial haemorrhages which are the most feared complication. Because of that many patients do not receive anticoagulants; particularly patients at risk of falls or with history of falls. It is unclear what anticoagulant treatment these patients should be offered, and the Liverpool AF-Falls Project aims to investigate this area. Purpose: This systematic review and meta-analysis aimed to determine the most appropriate anticoagulant treatment option for the management of atrial fibrillation patients at risk of falls or with a history of falls. Methods: We conducted a systematic review and meta-analysis, including studies evaluating safety and efficacy of different anticoagulants (Vitamin K Antagonist-VKA- versus Non-Vitamin K Antagonist Oral Anti-Coagulants-NOAC). Outcomes were ischemic stroke, major bleeding, intracranial haemorrhage, haemorrhagic stroke and mortality. Bibliographic databases (CENTRAL, CINAHL, ClinicalTrials.gov, EMBASE, MEDLINE, Scopus and Web of Science) were searched. Two independent reviewers identified studies, extracted data, and assessed the risk of bias using the Cochrane Risk of Bias 2 tool for randomized clinical trials and with the Newcastle-Ottawa-Scale for observational studies. Pairwise meta-analysis with random and fixed effects models were conducted. Heterogeneity was assessed with the I2 statistics. Hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs) were used to assess the effect of drugs on efficacy and safety. Results: 823 articles were identified, 643 after removing duplicates. 95 were screened for full text and 3 articles were retained for final quantitative synthesis including 26, 514 patients. Risk of bias was moderate in Rao et al. 2018 and Steffel et al. 2017, and low in Miao et al. 2019. In meta-analysis, the hazard for intracranial haemorrhage was lower with NOACs compared to VKA (hazard ratio (HR) 0.33, 95% confidence interval (CI) [0.13–0.82]; p<0, 001; I²=52%). There were no difference between NOACs and VKA regarding risks in ischemic stroke (HR 0.88, 95%CI [0.70–1.10; p=0.25; I²=0%), major bleeding (HR 0.88, 95%CI [0.62–1.27]; p=0.51, I²=0%); haemorrhagic stroke (HR 0.36, 95%CI [0.11–1.13]; p=0.08; I²=0%) and all-cause mortality (HR 0.95, 95%CI [0.67–1.33]; p=0.75; I² = 0%). Conclusions: NOACs were associated with less intracranial haemorrhages than VKAs. There were no statistically significant differences in other outcomes. However, limited number of studies were identified suggesting research gaps in the AF patients with increased falling risk or history of falls, requiring careful interpretation pending more evidence.